Kinetic AGN feedback effects on cluster cool cores simulated using SPH - Barai, Paramita (2016)
We implement novel numerical models of AGN feedback in the SPH code gadget-3, where the energy from a supermassive black hole (BH) is coupled to the surrounding gas in the kinetic form. Gas particles lying inside a bi-conical volume around the BH are imparted a one-time velocity (10 000 km s-1) increment. We perform hydrodynamical simulations of isolated cluster (total mass 1014 h-1 M⊙), which is initially evolved to form a dense cool core, having central T ≤ 106 K. A BH resides at the cluster centre, and ejects energy. The feedback-driven fast wind undergoes shock with the slower moving gas, which causes the imparted kinetic energy to be thermalized. Bipolar bubble-like outflows form propagating radially outward to a distance of a few 100 kpc. The radial profiles of median gas properties are influenced by BH feedback in the inner regions (r < 20-50 kpc). BH kinetic feedback, with a large value of the feedback efficiency, depletes the inner cool gas and reduces the hot gas content, such that the initial cool core of the cluster is heated up within a time 1.9 Gyr, whereby the core median temperature rises to above 107 K, and the central entropy flattens. Our implementation of BH thermal feedback (using the same efficiency as kinetic), within the star formation model, cannot do this heating, where the cool core remains. The inclusion of cold gas accretion in the simulations produces naturally a duty cycle of the AGN with a periodicity of 100 Myr.